2017
DOI: 10.1128/aac.02461-16
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of the CroRS Two-Component System for Resistance to Cell Wall-Targeting Antimicrobials in Enterococcus faecium

Abstract: Enterococci are serious opportunistic pathogens that are resistant to many cell wall-targeting antibiotics. The CroRS two-component signaling system responds to antibiotic-mediated cell wall stress and is critical for resistance to cell wall-targeting antibiotics in Enterococcus faecalis. Here, we identify and characterize an orthologous two-component system found in Enterococcus faecium that is functionally equivalent to the CroRS system of E. faecalis. Deletion of croRS in E. faecium resulted in marked susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 40 publications
(44 reference statements)
2
46
0
Order By: Relevance
“…Mueller-Hinton broth (MHB) was used for growth of E. faecalis in all experiments. Markerless allelic exchange was used to construct chromosomal mutations in the genome of E. faecalis OG1, as described previously (42,43). Antibiotic resistance was determined by the broth microdilution method after 24 h at 37°C in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…Mueller-Hinton broth (MHB) was used for growth of E. faecalis in all experiments. Markerless allelic exchange was used to construct chromosomal mutations in the genome of E. faecalis OG1, as described previously (42,43). Antibiotic resistance was determined by the broth microdilution method after 24 h at 37°C in 96-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…The method described by Varadarajan and colleagues (50,51) was used to identify V71G as a candidate substitution in RepA to provide temperature sensitivity. We previously showed that the V71G substitution provides temperature-sensitive replication of a closely related vector (48). Inverse PCR on pCJK245 was used to introduce the V71G substitution into RepA.…”
Section: Methodsmentioning
confidence: 99%
“…They are not, however, sufficient for resistance, since other proteins that are required for resistance expression have been found. In E. faecalis, the CroRS regulatory locus is required for cephalosporin resistance, as is a serine-threonine eukaryote-like kinase, IreK (also known as Stk) (160,161). The presence of genes for two of the three E. faecalis class A PBPs (ponA and pbpZ) is also required for resistance to cephalosporins in E. faecalis (141).…”
Section: Acquired Antimicrobial Resistance Resistance To ␤-Lactamsmentioning
confidence: 99%